What Lies Beneath Writer's Block? Exploring the Dimensions of Writing Anxiety - Patty, Jusak (PT. Riset Press International, 2025)
This study examines the three types of writing anxiety—somatic, cognitive, and avoidance—through library research methodology. Writing anxiety represents a significant barrier to effective written communication in educational and professional contexts. The research addresses three main questions: the characteristics and manifestations of each anxiety type, the factors that contribute to their development, and effective coping strategies. Through literature review and analysis of relevant literature published between 2018 and 2024, the study identifies distinct manifestations of each anxiety type: physical symptoms for somatic anxiety, negative thought patterns for cognitive anxiety, and task-avoidant behaviors for avoidance anxiety. Contributing factors include previous negative experiences, problematic educational practices, personal characteristics, situational elements, and social influences. Effective coping strategies include cognitive approaches that challenge negative beliefs, behavioral techniques like establishing writing routines, educational supports such as writing workshops, physical management strategies including relaxation exercises, and environmental modifications. The findings provide valuable insights for educators, writing support professionals, and individuals struggling with writing anxiety, highlighting the importance of comprehensive, multi-dimensional approaches to address this complex phenomenon.